The Engineering of Mixed Reality Systems - Dubois, Emmanuel; Gray, Philip; Nigay, Laurence (Human-Computer Interaction Series, 2010)
Mixed reality computer systems aim to fuse digital and physical information and features, either as an augmentation of real-world environments or as a means of providing physically-based interaction with computer-based systems. So - for example - museum displays can be augmented with added information about their history and provenance, and this information delivered to a visitor via their mobile telephone as they pass in front of the display. An increasing number of systems are exploiting mixed reality but to date there are no systematic methods, techniques or guidelines for the development of such systems. In bringing together contributions on a broad range of mixed reality development issues this book provides a sound theoretical foundation for a disciplined approach to mixed reality engineering. Divided into three parts, interaction design, software design and implementation, this book brings together state of the art developments in the engineering of mixed reality systems, addressing issues at these three levels. Part 1 covers generic and specific mixed reality design elements and provides an overview of the design method; Part 2 addresses technical solutions for interaction techniques, development tools and a global view of the mixed reality software development process. Finally part 3 contains detailed case studies to highlight the application of mixed reality in a variety of fields including aviation, architecture, emergency management, games, and healthcare. Multimodal and tangible interaction designers, systems engineers working in augmented reality and ubiquitous systems, human factors researchers, and others interested in the use of mixed reality techniques in their work, will find this book a useful addition to their bookshelf.